Stark Helmet / Muhammad Fareez Basri, Muhammad Shazwan Mohd Noh ... [et al.] - Basri, Muhammad Fareez; Mohd Noh, Muhammad Shazwan; Abdullah, Noor Farah Eliana; Mohd Rani, Rabi'atul 'Adawiyah; Maulan, Siti Adilah (2019)
The team has decided to develop the Stark Helmet as a Blueprint. Stark helmet is to protect the user while riding a motorcycle. The Team achieve that by increasing visibility, reducing noise distractions, and allowing connectivity. The Team product combines integrated head-up display varieties of functions and features. It is the smartest motorcycle helmet ever made. Stark Helmets targeted the user who is a riders or motorcyclist. This is because, these rider soften experience problems such as have trouble making calls even over the wireless since the environment is too noisy. Besides, the motorcyclist also having trouble viewing maps as they need to focus on driving ahead. Therefore, they can be lost